The Origin of Workerless Parasites in Leptothorax (S. Str.) (Hymenoptera: Formicidae) - Jürgen Heinze (Psyche: A Journal of Entomology)
The evolutionary origin of workerless parasitic ants parasitizing colonies of Leptothorax (s.str.) is investigated using data on morphology, chromosome number, and allozyme phenotype of both social parasites and their hosts. Of the three previously proposed pathways, the evolution of workerless parasites from guest ants or slave-makers is unlikely, at least according to a phenogram obtained by UPGMA clustering of Nei's similarities based on seven enzymes, lntraspecific evolution of the workerless parasites Doronomyrmex goesswaldi, D. kutteri, and D. pacis from their common host, Leptothorax acervorum cannot be excluded with the present data. The workerless parasite L. paraxenus, however, clearly differs from its host, L. cf. canadensis, in morphology and biochemistry, and most probably did not evolve from the latter species. It is proposed to synonymize Doronomyrmex under Leptothorax (s.str.).